The beginnings of the european diplomatic service from the 1950s to the 1980s - Pajtinka, Erik (Teorija in praksa, 2020)
This article examines the development of the European Communities (EC) diplomatic service in the pre-Lisbon period. More specifically, it maps the period from the 1950s, when the first non-diplomatic offices in foreign countries with limited powers were opened, until the end of 1980s, when a network of European missions with full diplomatic status became a reality. It is concluded that the EC diplomatic service has its roots in the establishment of two types of EC foreign representation, differing in their primary purpose, status and tasks. The development of these two EC representation types entailed quite different dynamics, as shown in the different speeds of their transformation to become "traditional" diplomatic representations
Keywords: Diplomatic and consular service; Diplomatska in konzularna služba; diplomatske službe; European union; Evropska komisija; Evropska unija; Foreign policy; zgodovinski razvoj; Zunanja politika